Distribution Patterns of Vector Snails and Trematode Cercaria in their Vectors in Some Selected Areas of Mymensingh (Journal of Environmental Science and Natural Resources, 2013)
Different species of vector snails carry larval stages of different trematodes. Studies were performed to investigate different snail species and parthinate of trematodes carried by them, in some selected areas of Mymensingh Sadar, Mymensingh. Snails were collected by hand picking method and examined after crushing. Among 864 tested snails, it revealed the presence of six species of snails like Lymnaea auricularia 145 (16.8%), Lymnaea luteola 205 (23.7%), Indoplanorbis exustus 273 (31.6%), Vivipara spp. 164 (18.9%), Brotia spp. 35 (4.1%) and Pila spp. 42 (4.8%) in the study areas. Among them 5.8% L. luteola and 6.2% L. auricularia were infected with gymnacephalus cercariae. Again, 1.4% L. auricularia and 1.8% I. exustus were infected with echinostome cercaria. In this study, 1.8% Vivipara spp. and 2.6% I. exustus were positive for furcocercus cercaria. On the other hand, 1.8% Vivipara spp. was positive for xiphidocercus cercariae and 1.8% I. exustus was also positive for amphistome cercariae. One or more species of snails were found to harbor single or mixed types of cercariae such as gymnacepahlus, echinostome and furcocercous. Population densities of different species of snails were determined in per unit time which were statistically significant (p